The assembly of the major outer membrane protein OmpF of Escherichia coli depends on lipid synthesis. - Bolla, J M (1988)
Cerulenin, a drug which specifically blocks lipid synthesis, prevented both the trimerization of OmpF monomers and their assembly into the outer membrane of Escherichia coli B cells. A monoclonal antibody directed against a surface-exposed epitope of the trimer was used to probe the assembly of OmpF in the presence or absence of the drug. An inhibition level of 80% was reached 16 min after the addition of cerulenin. The accumulated monomeric form could not be assembled even after lipid synthesis was restored. Instead, it was slowly degraded. It was further shown that the inhibition of assembly resulted in a rapid inhibition of OmpF synthesis. These data demonstrate that there is a direct relationship between the synthesis of lipid (most likely lipopolysaccharide) and the correct export of OmpF. This coupling is required to promote the trimerization of the porin monomer and its assembly into the outer membrane.